DEFECTOLOGICAL PRACTISE FROM THE PERSPECTIVE OF NEXT GENERATION GENETICS - Mihajlović, Nevenka K; Mihajlović, Milica Lj; Mihajlović, Ljubiša M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
Defectologists not only discover and study people with certain mental and physical disabilities they also help these people by giving them the opportunity to lead a normal life. From the aspect of modern human and molecular genetics the job of a defectologist should be associated with people who some form of a genetic defect, also known as a "genetic error"-mutation. This is the reason why a defectologist (in order to be a successful one) has to know what is nature and type of the mutation that patient has, in other words he must find out the genetic diagnosis of the patient. However, the practice in our the conditions such as ours is a little different, most of the times the diagnosis is incomplete and does not give information about the true cause of the problem, this means that it gives only information about the symptoms but not about the true origin of the problem. Due to this fact the main focus of a defectologist is to properly diagnose the problem from a genetic perspective. A proper genetic diagnosis involves finding out what genetic mutation lays at the heart of the disease(also the molecular mechanisms of the diseases should be known). This approach has two benefits: (A) successful treatment and rehabilitation of the patient and (B) figuring out the future perspective of the patient. The genetic diagnosis is discovered by a multidiscipline team of experts: genetic counselors, defectologists , doctors and psychologist. The first step in finding out the genetic diagnosis is evaluating the patient and his/her family, later on we can use a genetic once have an idea that the nature of patients condition is indeed genetic. This is why the education of defectologist is needed in order to for them to know about the genetic factors that influence the appearance and the development of the patient's condition. This form of education should allow defectologist to get a better understanding of the potential of modern genetic techniques in precisely determining the genetic bases of the disease. By doing so the quality of their work would be vastly improved and modernized.
Keywords: defectological practice; EDUCATION; genetic diagnosis; defectology